Automatic selection of resting-state networks with functional magnetic resonance imaging - Storti, Silvia Francesca; Formaggio, Emanuela; Nordio, Roberta; Manganotti, Paolo; Fiaschi, Antonio; Bertoldo, Alessandra; Toffolo, Gianna Maria (Frontiers in Neuroscience, 2013)
Functional magnetic resonance imaging (fMRI) during a resting-state condition can reveal the co-activation of specific brain regions in distributed networks, called resting-state networks, which are selected by independent component analysis (ICA) of the fMRI data. One of the major difficulties with component analysis is the automatic selection of the ICA features related to brain activity. In this study we describe a method designed to automatically select networks of potential functional relevance, specifically, those regions known to be involved in motor function, visual processing, executive functioning, auditory processing, memory, and the default-mode network. To do this, image analysis was based on probabilistic ICA as implemented in FSL software. After decomposition, the optimal number of components was selected by applying a novel algorithm which takes into account, for each component, Pearson's median coefficient of skewness of the spatial maps generated by FSL, followed by clustering, segmentation, and spectral analysis. To evaluate the performance of the approach, we investigated the resting-state networks in 25 subjects. For each subject, three resting-state scans were obtained with a Siemens Allegra 3 T scanner (NYU data set). Comparison of the visually and the automatically identified neuronal networks showed that the algorithm had high accuracy (first scan: 95%, second scan: 95%, third scan: 93%) and precision (90%, 90%, 84%). The reproducibility of the networks for visual and automatic selection was very close: it was highly consistent in each subject for the default-mode network (≥ 92%) and the occipital network, which includes the medial visual cortical areas (≥ 94%), and consistent for the attention network (≥ 80%), the right and/or left lateralized frontoparietal attention networks, and the temporal-motor network (≥ 80%). The automatic selection method may be used to detect neural networks and reduce subjectivity in ICA component assessment.